Paresthesia‐Free Dorsal Root Ganglion Stimulation: An ACCURATE Study Sub‐Analysis. Issue 2 (12th March 2019) - Mekhail, Nagy; Deer, Timothy R.; Kramer, Jeffery; Poree, Lawrence; Amirdelfan, Kasra; Grigsby, Eric; Staats, Peter; Burton, Allen W.; Burgher, Abram H.; Scowcroft, James; Golovac, Stanley; Kapural, Leonardo; et al.
Abstract : Introduction: ACCURATE, a randomized controlled trial comparing dorsal root ganglion (DRG) stimulation to spinal cord stimulation, showed that DRG stimulation is a safe and effective therapy in individuals with lower extremity chronic pain due to complex regional pain syndrome (CRPS) type I or II. Investigators noted that DRG stimulation programming could be adjusted to minimize, or eliminate, the feeling of paresthesia while maintaining adequate pain relief. The present study explores treatment outcomes for DRG subjects who were paresthesia‐free vs. those who experienced the sensation of paresthesia, as well as the factors that predicted paresthesia‐free analgesia. Methods: A retrospective analysis of therapy outcomes was conducted for 61 subjects in the ACCURATE study who received a permanent DRG neurostimulator. Outcomes of subjects who were paresthesia‐free were compared to those who experienced paresthesia‐present therapy at 1, 3, 6, 9, and 12‐month follow‐ups. Predictor variables for the presence or absence of paresthesias with DRG stimulation were also explored. Results: The percentage of subjects with paresthesia‐free pain relief increased from 16.4% at 1‐month to 38.3% at 12‐months. Paresthesia‐free subjects generally had similar or better outcomes for pain severity, pain interference, quality of life, and mood state as subjects with paresthesia‐present stimulation. Factors that increased the odds of a subject feeling paresthesia were higher stimulation amplitudes and frequencies, number of implanted leads, and younger age. Conclusions: Some DRG subjects achieved effective paresthesia‐free analgesia in the ACCURATE trial. This supports the observation that paresthesia is not synonymous with pain relief or required for optimal analgesia with DRG stimulation.